PENGARUH KEPEMIMPINAN DAN PERILAKU INOVASI GURU TERHADAP MUTU PENDIDIKAN, PRESTASI BELAJAR DAN KESEMPATAN KERJA (Studi Pada Karyawan PT PLN (Persero) Unit Induk Pembangunan VIII Surabaya) - Prasetya, Eka Mulya; Afrianty, Tri Wulida; Prasetya, Arik (FIA UB, 2020)
The purpose of this paper is to find out the extent of the role of the principal managing the school with his leadership and teachers who work innovatively in teaching and learning activities capable of providing high quality education which will ultimately have an impact on student achievement and opportunities or employment opportunities for graduates. This paper extends an empirical review of the role of teachers in improving the quality of education in order to get the most out of students' learning achievements and get work opportunities for graduates. The role of school principals in managing schools with their leadership and teachers who work innovatively in teaching and learning activities is able to provide a good quality of education in order to get the maximum student achievement and provide employment opportunities or opportunities for graduate students. Existing research only addresses the point of view of students and students who have graduated. Even though the role of teachers is key in realizing the quality of education implemented in schools so that students are able to have abilities that are useful for survival after graduation..